Outcoupling efficiency of organic light‐emitting diodes depending on the fill factor and size of the microlens array. Issue 8 (5th June 2014) - Hwang, Deok Hyeon; Kwon, Ow Tae; Lee, Won Jae; Hong, Jin Woong; Kim, Tae Wan
<x xml:space="preserve">Abstract</x> The outcoupling efficiency (OCE) of organic light‐emitting diodes (OLEDs) incorporating a microlens array was investigated depending on the fill factor, radius, and shape of the microlens through simulation and experiment. We simulated the OCE of the device that consisted of a reflective layer, an emissive layer, and a flat transparent substrate. In this device, the OCE of 22% was obtained. In order to investigate the outcoupling effect, eleven microlens arrays were made and applied to the OLEDs. An optimum fill factor of 0.30 was found from the simulation and confirmed by experiment. The experimental results of the OCE depending on the fill factor and the radius of the microlens are close to those of the simulation of the trapezoidal shape of microlens. It was found that the OCE is a little more affected by the fill factor rather than the size of the microlens.